1974
DOI: 10.1039/c39740000257
|View full text |Cite
|
Sign up to set email alerts
|

The stereochemistry of electrophilic addition to tricarbonyldieneiron complexes

Abstract: G12 SQQ)Summary The X-ray structural analysis of a substituted uncertainty exists over both the regio-and stereo-specificity tricarbonylallyliron cationic intermediate unambigu-of electrophilic attack on unsaturated ligands. I t has been ously demonstrates that tricarbonyl(trans, trans-hexa-2,k predicted' that the electron density in the .rr-orbital of a diene)iron undergoes stereospecific endo attack under complexed ligand will be greatest in the bonding region Friedel-Crafts conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Figures 1 and 2 4)) = 2.010 (2) Á. Because the central allylic carbon atom C(4) lies in a crystallographic mirror plane, the two allylic C-C bonds are equal, 1.409 (2) Á, and in agreement with values recently reported for the structures of |[t,3-(H3C)C2H3-(CHCH3C(0)CH3)]Fe(CO)3j+ (1.384 (15), 1.404 (16) A), 15 [(C2H5)2B(C3N2H3)2](t,3-C3H5)(C3N2H4)(CO)2Mo (1.387 (6), 1.412 (6) A),16 and [(C2H5)2B(C3N2H3)2] [t,3-CH2C-(C6H5)CH2](CO)2Mo (1.393 (10), 1.411 (10) A).17…”
Section: Description Of the Structuressupporting
confidence: 90%
“…Figures 1 and 2 4)) = 2.010 (2) Á. Because the central allylic carbon atom C(4) lies in a crystallographic mirror plane, the two allylic C-C bonds are equal, 1.409 (2) Á, and in agreement with values recently reported for the structures of |[t,3-(H3C)C2H3-(CHCH3C(0)CH3)]Fe(CO)3j+ (1.384 (15), 1.404 (16) A), 15 [(C2H5)2B(C3N2H3)2](t,3-C3H5)(C3N2H4)(CO)2Mo (1.387 (6), 1.412 (6) A),16 and [(C2H5)2B(C3N2H3)2] [t,3-CH2C-(C6H5)CH2](CO)2Mo (1.393 (10), 1.411 (10) A).17…”
Section: Description Of the Structuressupporting
confidence: 90%
“…Since the time of the work by Hallam and Pauson, the chemistry of acyclic and cyclic (1,3-diene)iron tricarbonyl complexes has become an active research area and some interesting reactions of (butadiene)iron tricarbonyl itself and of many new substituted (butadiene)iron tricarbonyl complexes have been reported. For instance, (butadiene)iron tricarbonyl reacted with acetic anhydride in CH 2 Cl 2 in the presence of AlCl 3 to give the 1-acetyl derivative 11a. Competition studies 11a showed (C 4 H 6 )Fe(CO) 3 to have a Friedel−Crafts reactivity similar to that of ferrocene (which Woodward and Rosenblum had shown to be a superelectrophile).…”
mentioning
confidence: 99%
“…Competition studies 11a showed (C 4 H 6 )Fe(CO) 3 to have a Friedel−Crafts reactivity similar to that of ferrocene (which Woodward and Rosenblum had shown to be a superelectrophile). Later work showed that Friedel−Crafts acylation of (butadiene)iron tricarbonyl proceeds via a substituted allyliron tricarbonyl cation intermediate in which the acyl oxygen atom is coordinated to the iron atom 11b…”
mentioning
confidence: 99%
“…This type of approach has not previously been used in the case of cyclohexadiene ligands and Fe(CO) 3 . The 4-methoxy-1-cyclohexa-1,3-dieneacetic acid derivative was chosen on the basis of the previous proposed coordination of the carbonyl group to Fe(CO) n during complexation . Furthermore this complex has been shown to be an important building block for the iron-mediated diastereoselective synthesis of spirocycles …”
mentioning
confidence: 99%